Pengaruh Kualitas Pelayanan, Harga dan Promosi Terhadap Kepuasan Pelanggan dengan Menggunakan Outsourcing PT. Jangkar Putra Indonesia - Ratih Millenia Wardani; Andriansyah Bachtillah Putra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to examine the influence of service quality, price and promotion on customer satisfaction by using outsourcing PT. Indonesian Men's Anchor. The type of data used in this research is primary data. The method used in this research is a quantitative research method. The population in this study are customers of PT. Jangkar Putra Indonesia and the number of samples in this study were 113 customers. The data collection method uses a survey method, with the research instrument being a questionnaire. The analysis technique used is multiple linear regression analysis using SPSS Version 25 data processing software. The results of the study indicate that service quality has a positive and significant effect on customer satisfaction. Price has a positif and significant effect on customer satisfaction. Promotion has a positive and significant effect on customer satisfactions.